Kedelai Dalam Jurnal Penelitian Pertanian Tanaman Pangan Periode 2011 – 2021: Studi Bibliometrika - Yupi Royani; Rochani Nani Rahayu (Jurnal Gema Pustakawan, 2022)
Bibliometric analysis was used to find out the research on soybeans that had been carried out, and recorded in the Journal of Food Crops Agricultural Research. 2012–2021 period. The data is accessed from the address http://ejurnal.litbang.pertanian.go.id/, and the data recorded is data relating to articles published every year, keywords in articles, authors, institutions where the authors work, and cities. where the writer works. Furthermore, the collected data is processed using the percentage of frequency, and presented in tabular form, the results are analyzed, discussed and ended with drawing conclusions. The results showed that during 2011-2021 266 articles were published, and the distribution of articles by volume showed that the highest number of articles was in volume 30 (29 articles; 10.9%), and number 2 was more (94 articles; 35, 21%). The pattern of authorship is dominated by articles written in collaboration (245 articles: 92.11%) compared to single authors (21 articles; 7.89%). Made Jana Mejaya and Muhammad Azrai were the most prolific writers during 2011-2021 with 11 articles each. The most published articles in the Journal of Food Crops Agriculture came from the Bogor Agricultural Institute, which was 80 articles. The city where the author works the most is Bogor with a frequency of 141. Keyword analysis shows that Rice is the most frequent keyword, with 124 articles. The conclusion shows that based on the results of research for 11 years, it turns out that researchers have studied more about rice than about soybeans.